STANDARISASI ALAT UKUR, TAKAR, TIMBANG, DAN PERLENGKAPANNYA DI PASAR TRADISIONAL DALAM MENJAMIN HAK KONSUMEN: Standardization of Measuring, Weighing, and Related Instruments in Traditional Markets to safeguard Consumer Rights - Triani Nabila Diaqilah Surmana; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2026)
The use of measuring, weighing, and filling instruments and their accessories plays a crucial role in commercial transactions in traditional markets, as it directly affects the accuracy of product quantities and prices paid by consumers. Inaccurate instruments can cause consumer losses and violate the right to accurate, clear, and honest information. This article examines how consumer rights can be protected through the proper use of measuring, weighing, and filling instruments and how standardization is implemented in traditional markets. This study employs normative legal research using a regulatory approach, supported by an analysis of primary and secondary legal materials. The findings indicate that standardization through calibration and recalibration serves as an essential legal mechanism to ensure measurement accuracy and promote orderly trade practices. However, its implementation remains suboptimal due to low compliance among business actors and insufficient supervision. Therefore, strengthening supervision and law enforcement is necessary to ensure effective consumer protection in traditional markets.